Personalized pricing when consumers can purchase multiple items - Qiuyu Lu; Noriaki Matsushima (Osaka University, Institute of Social and Economic Research (ISER), 2022)
We discuss the effect of personalized pricing on profits and welfare in a Hotelling model in which consumers can simultaneously purchase from both firms. As the additional gain from the second purchase increases, personalized pricing is more likely to harm (resp., benefit) consumers (resp., firms). If the additional gain is interme- diate, personalized pricing improves consumer welfare and firms' profits, contrasting with the standard result: personalized pricing benefits consumers but harms firms. When firms can choose one of the pricing policies: uniform or personalized, both choose uniform (resp., personalized) pricing under some parameters (resp., in any case); multiple equilibria can co-exist.
Keywords: L13; D43; 330; Personalized pricing; Multi-unit purchase; Hotelling model